Overconfidence and hygiene non-compliance in hospitals - Katharina Lima de Miranda; Lena Detlefsen; Michael Stolpe (Kiel Institute for the World Economy (IfW), 2020)
Among measures to fight hospital acquired infections, an emerging epidemic in many countries around the world, adoption of appropriate hand hygiene practices by healthcare workers is considered a priority. Despite their simplicity and effectiveness, healthcare workers' compliance is poor, with most empirical studies finding compliance rates well below 50% in many countries. Management strategies to increase compliance are often based on the notion that non-compliance is a moral hazard problem, characterized by asymmetric information between hospital management and healthcare workers. In this study, we provide empirical evidence that an individual behavioral characteristic, known as overconfidence, induces many healthcare workers to overestimate their hand hygiene compliance and hence to underperform unknowingly and unintentionally [...].
Keywords: I12; I18; C91; 330; hospital acquired infections; hand hygiene; overconfidence; moral hazard; WHO guidelines